Retrospective Analysis of Radiation Exposure During Endoscopic Retrograde Cholangiopancreatography: Critical Determinants. (2011) - Kim, Edward; McLoughlin, Mark; Lam, Eric C; Amar, Jack; Byrne, Michael; Telford, Jennifer; Enns, Robert
Abstract : BACKGROUND: Fluoroscopy during endoscopic retrograde cholangiopancreatography (ERCP) has a logarithmic relationship with radiation exposure, and carries a known risk of radiation exposure to patients and staff. Factors associated with prolonged fluoroscopy duration have not been well delineated. OBJECTIVES: To determine the specific patient, physician and procedural factors that affect fluoroscopy duration. METHODS: A retrospective analysis of 1071 ERCPs performed at two tertiary care referral hospitals over an 18-month period was conducted. Patient, physician and procedural variables were recorded at the time of the procedure. RESULTS: The mean duration of 969 fluoroscopy procedures was 4.66 min (95% CI 4.38 to 4.93). Multivariable analysis showed that the specific patient factors associated with prolonged fluoroscopy duration included age and diagnosis (both P<0.0001). The endoscopist was found to play an important role in the duration of fluoroscopy (ie, all endoscopists studied had a mean fluoroscopy duration significantly different from the reference endoscopist). In addition, the following procedural variables were found to be significant: number of procedures, basket use, biopsies, papillotomy (all P<0.0001) and use of a tritome (P=0.004). Mean fluoroscopy duration (in minutes) with 95% CIs for different diagnoses were as follows: common bile duct stones (n=443) 5.12 (3.05 to 4.07); benign biliary strictures (n=135) 3.94 (3.26 to 4.63); malignant biliary strictures (n=124) 5.82 (4.80 to 6.85); chronic pancreatitis (n=49) 4.53 (3.44 to 5.63); bile leak (n=26) 3.67 (2.23 to 5.09); and ampullary mass (n=11) 3.88 (1.28 to 6.48). When no pathology was found (n=195), the mean fluoroscopy time was 3.56 min (95% CI 3.05 to 4.07). Comparison using t tests determined that the only two diagnoses for which fluoroscopy duration was significantly different from the reference diagnosis of 'no pathology found' were common bile duct stones (P<0.0001) and malignant strictures (P<0.0001). CONCLUSIONS: Factors that significantly affected fluoroscopy duration included age, diagnosis, endoscopist, and the number and nature of procedures performed. Elderly patients with biliary stones or a malignant stricture were likely to require the longest duration of fluoroscopy. These identified variables may help endoscopists predict which procedures are associated with prolonged fluoroscopy duration so that appropriate precautions can be undertaken.